Assumptions, Applications and Implications of Modern Economic Analysis in Comprehending Neo-Classical Economics - Nicole Dubois (Social Science Chronicle)
This research paper delves into the foundational principles, assumptions, applications, and limitations of neoclassical economics, presenting a comprehensive exploration of its significance in economic analysis, policy formulation, and the understanding of market behaviour. Neoclassical economics serves as a fundamental framework that shapes economic theories, models, and policy decisions. The paper embarks on an exploration of key concepts within neoclassical economics, starting with the foundational assumptions of rationality in decision-making. The assumption of perfect rationality underpins economic analyses, offering a framework for understanding individual and firm behaviour. However, emerging insights from behavioural economics challenge this assumption, highlighting cognitive biases and deviations from perfect rationality, thereby necessitating a more nuanced understanding of human decision-making. The study delves into the fundamental concept of supply and demand, elucidating its role in market interactions and price determination. The idealized assumption of perfect competition within neoclassical economics sets the stage for market efficiency, but the realities of imperfect markets, asymmetries in information, and externalities complicate this assumption, impacting the efficiency of resource allocation. Additionally, the concept of rational expectations posits that economic agents make predictions based on all available information, yet uncertainties and unforeseen events in the real world challenge this assumption. The paper discusses the implications of these assumptions in economic analysis, policy formulation, and market efficiency, emphasizing the need to integrate insights from emerging economic paradigms like behavioural and institutional economics. The implications of the study extend to economic modelling, policy formulation, and education, suggesting the need for a multidisciplinary approach to economic analysis. This research paper provides a critical analysis of neoclassical economics, acknowledging its foundational significance while advocating for the integration of alternative economic paradigms to refine economic analyses, policy formulations, and our understanding of market dynamics.